2021
DOI: 10.35848/1347-4065/abdcae
|View full text |Cite
|
Sign up to set email alerts
|

Importance of crystallinity improvement in MoS2 film by compound sputtering even followed by post sulfurization

Abstract: The MoS2 film for chip-size area was synthesized by two step processes consisting of MoS2-compound sputtering and post sulfurization. We intentionally revealed that the crystallinity of sulfurized MoS2 film depends on that of just-after-sputtered film. Therefore, a crystallinity improvement just-after sputtering is mandatory to achieve an excellent quality MoS2 film after sulfur-vapor annealing for thin film transistor, sensor and human interface device applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…1(a) show that the peak of the (002) plane, which indicates the c-axis orientation of the MoS 2 film, is present in all the samples. Similar shaped peaks with our results have been reported in polycrystalline TMDC thin films formed horizontally on the substrate surface by sputtering, 43,45) therefore the MoS 2 films in this study are considered to have a similar crystal structure whether with or without Nb doping. The in-plane measurements in Fig.…”
Section: Resultssupporting
confidence: 89%
“…1(a) show that the peak of the (002) plane, which indicates the c-axis orientation of the MoS 2 film, is present in all the samples. Similar shaped peaks with our results have been reported in polycrystalline TMDC thin films formed horizontally on the substrate surface by sputtering, 43,45) therefore the MoS 2 films in this study are considered to have a similar crystal structure whether with or without Nb doping. The in-plane measurements in Fig.…”
Section: Resultssupporting
confidence: 89%
“…14) Previously, we synthesized atomic-layer TMDC films with thicknesses of a few nanometers using ultra-high vacuum (UHV) RF magnetron sputtering. [15][16][17][18][19][20][21] Recently, we found that grain size and crystallinity in the PVD WS 2 film are respectively enlarged and enhanced by low sputtering power, which increases resistivity and activation energy. 22) In addition, the number of layers modulates the thermoelectric characteristics of the TMDC films, 2,23) which are measured by on-chip thermoelectric devices composed of thermoelectric material, a heater and thermometers.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, a combination of sputtering and sulfur vapor annealing (SVA) was used to realize layered-polycrystalline TMDC films with a low carrier density, large area and uniform thickness [16]- [18], resulting in normally off MoS 2 nMISFETs [19] and ZrS 2 ambipolar-MISFETs [20]. Compared to MoS 2 and ZrS 2 films, the WS 2 has the advantages of a higher calculated mobility than MoS 2 film and lower mass anisotropy than ZrS 2 film.…”
Section: Introductionmentioning
confidence: 99%